Drug-induced panniculitis due to deworming in a dog – case report - Nitta, Cayo Yuji; Gennari, Solange Maria; Ferreira, Juliana Isabel Giuli da Silva; Galati, Leandro Haroutune Hassesian; Larsson, Carlos Eduardo (Brazilian Journal of Veterinary Research and Animal Science, 2017)
Outpatient clinics, clinics, and veterinary hospitals in the state of São Paulo and other Brazilian states commonly prescribe broad-spectrum vermicidal agents. The prescriptions are not based on coproparasitological examination results and drugs, including those used for the elimination of enteric parasites, are not innocuous and can potentially cause health hazards. Therefore, we report a clinical case of drug-induced panniculitis caused by deworming and show the actual occurrence of endoparasites in canine and feline outpatients at HOVET-USP.